THE ENHANCEMENT OF CYBERSECURITY AND ECONOMIC GROWTH: PANEL DATA ANALYSIS - ÜNVER, Gül Nazik; KOLAT, Şerife Deniz (Cyberpolitik Journal, 2025)
This study aims to comprehensively analyze how economic growth influences cybersecurity investments and policies in contemporary economies where digitalization is spreading at an accelerated pace. In an era characterized by mounting direct and indirect expenses stemming from cyber threats to the global economy, there is a pressing need to elucidate the correlation between cybersecurity and macroeconomic performance quantitatively. The present study examines the relationship between cybersecurity capacity and economic growth using a multidimensional nested panel data analysis method, which utilizes annual data for 171 countries in the IDI. The study also reveals that cybersecurity isn’t just a technical issue but one of the main determinants of macroeconomic stability. In nations undergoing digital transformation, cybersecurity infrastructure is as strategically significant as traditional infrastructure investments. This study examines the relationship between economic growth and cybersecurity. The findings suggest that there is a statistically significant and positive relationship between cybersecurity and economic growth. The objective of this study is to provide policymakers with strategic recommendations by highlighting the critical role of economic growth in cybersecurity, supported by quantitative data.